Optimal control problem for the BCF model describing crystal surface growth - Zhao, Xiaopeng; Cao, Jinde (Nonlinear Analysis: Modelling and Control, 2016)
In this paper, for the BCF model describing crystal surface growth, the optimal control problem is considered, the existence of optimal solution is proved and the optimality system is established.